1994
DOI: 10.1099/0022-1317-75-6-1353
|View full text |Cite
|
Sign up to set email alerts
|

Linear antigenic and immunogenic regions of the respiratory syncytial virus P protein

Abstract: Three linear antigenic regions on the P protein from human respiratory syncytial virus (RSV) subgroup A (strain A2) were represented by peptides that reacted with monoclonal antibodies and with sera from humans with recent or previous RSV infection. The determinants were localized within three hydrophilic regions of the P protein: Prog~ to AspH0, Ser16~ to LySls 0 and Glu221 to Phe241. The role of individual amino acids in the epitopes defined by monoclonal antibodies was determined. Two monoclonal antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Recently we reported similar studies of the RSVP protein (Leonov et al, 1994). In the present study, we identified three immunodominant linear antigenic regions by use of synthetic overlapping peptides representing the RSV N protein.…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…Recently we reported similar studies of the RSVP protein (Leonov et al, 1994). In the present study, we identified three immunodominant linear antigenic regions by use of synthetic overlapping peptides representing the RSV N protein.…”
Section: Introductionmentioning
confidence: 66%
“…ELISA with purified RSV antigen and peptides was performed as previously described (Akerlind-Stopner et al, 1990;Leonov et al, 1994). The results were expressed either as A492 (mean of three determinations) or, for substituted peptide analogues, as the percentage of peptides binding.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations